The Use of Technologies in Second Language Learning: The Case of a Mexican University - Cueto, Maria del Carmen Hernandez; Ramos, Marcela Garcia; Garcia, Maria Georgina Ochoa; Cheol., Yun Sang (European Scientific Journal, ESJ, 2017)
Introduction: This research is about the use of technology in learning English as a Foreign Language at higher education in a public University in Mexico. This study is focused on how students use the technology for academic and non-academic issues to learn English. The object of the study a sample of twenty five percent of English language students (375 students) were considered. Students’ average age was 18-25. Methodology: For this research two instruments were used to gather data the first one a questionnaire designed for this purpose, the second one an interview to know what kind of gadgets students use to learn English in higher education and how this technology could be introduced in second language learning classrooms. The results: allowed concluding that most technological gadgets used by students were Cells and Laptops to surf the net and chat through social networks for non-academic issues and laptops and desktop computers to work on school duties with specific software.